SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PENERIMA BLT-DD MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Pangestu, Tri Agus Belly; Tursina, Tursina; Nyoto, Rudy Dwi (JUTECH : Journal Education and Technology, 2024)
The government implemented BLT-Dana Desa to alleviate poverty. In Teluk Kapuas Village, the distribution process is still manual, making it challenging for village officials to identify recipients. The BLT-Dana Desa scheme allows recipients to be determined participatively through village meetings, but without a definite method, this process is time-consuming and delays decision-making. To expedite the selection of BLT recipients, a Decision Support System (DSS) based on the Analytical Hierarchy Process (AHP) was developed. This application helps prioritize recipients based on criteria such as monthly income, housing conditions, dependents, age, and program participation. The AHP method simplifies complex problems into smaller, manageable parts, enabling objective and consistent evaluations. Testing with Black Box Testing and User Acceptance Test (UAT) showed the application met user expectations. UAT, conducted via a Google Form questionnaire using a Likert Scale, achieved an 88% approval rating from 5 respondents. The application is considered feasible for accelerating the BLT recipient selection process in Teluk Kapuas Village. Its implementation is expected to make aid distribution more efficient and targeted, supporting the government’s efforts to reduce poverty in the area.